Design and analysis of longitudinal trials of antimicrobial use at the end of life: to give or not to give? - Manisha Juthani-Mehta; Heather G. Allore (SAGE Publishing, 2019)
This perspective review considers analytic features of the design of a longitudinal trial regarding antimicrobial therapy in older terminal cancer patients receiving palliative care. We first overview antimicrobial use at the end of life; both the potential hazards and benefits. Antimicrobial prescribing should consider both initiation as well as cessation of medications when analyzing the burden of medications. Approaches to decision making regarding antimicrobial use are presented and the importance of health literacy in these decision processes. We next present aspects of both feasibility and comparative trial design with a health literacy intervention to reduce antimicrobial use in older terminal cancer patients receiving palliative care. Considerations to clustered randomization and given that infections can reoccur over a trial period, we share suggestions of longitudinal modeling of clustered randomized trial data.